Synthesis of porous carbon from a PVC polymer and its application in supercapacitors. Issue 12 (23rd May 2022) - Dhapola, Pawan Singh; Singh, Abhimanyu; Karakoti, Manoj; Singh, Manoj K.; Konwar, Subhrajit; Dohare, Sushil; Madkhli, Aysh Y.; Noor, I. M.; Singh, Pramod K.; Sahoo, Nanda Gopal
Abstract : In this study, the laboratory scale production of activated carbon synthesized from PVC with CoCl2 and H3 PO4, which is cheaper and has a good yield source material, is reported. Abstract : In this study, the laboratory scale production of activated carbon synthesized from PVC with CoCl2 and H3 PO4, which is cheaper and has a good yield source material, is reported. A prototype supercapacitor was successfully developed using activated carbon as an electrode material derived from the PVC polymer and IL (1-ethyl-3-methylimidazolium thiocyanate) as the electrolyte. The performance of the supercapacitor was estimated via electrochemical impedance spectroscopy, cyclic voltammetry, and the charge–discharge technique. The supercapacitor offered a high specific capacitance of ∼120 F g −1 at 5 m V s −1 . The performances of the supercapacitor were also estimated up to 15 days and up to 9000 cycles via cyclic voltammetry.